Estratégia em Call Centers: analisando o alinhamento com a práticas e tecnologias internas - Gião, Paulo Roberto (2006)
The call center (CC) industry has presented a rapid growth in many countries, it representing substantive part of workforce in these countries. This growth was stimulated by advances in technology information (IT) and for the nasty fall in data transmission and voice costs that occurred in last two decades due to telecommunications deregulation, meaning good opportunities for customer service centers implementation. This research is part of the Global Call Center Industry Project (GCCIP), a global study involving strategy, performance, human resources, technologies and institutional affairs in a greatest number of countries and call centers, which could provide a more complete vision of this industry. Twenty countries are participating in this project as United States, United Kingdom, Australia, India and Brazil. The coordination of the research in Brazil is in charge of PUC-SP. The main objective of this work is to analyze the strategic alignment among the answered strategy by organizations and their internal practices and utilized technologies in call center sector. Call centers are basically a great amount of people and technologies those are joined trough procedures and processes for the service realization regarding customer center proposal, since customer requests until outbound call for telemarketing operations. To try to identify and confirm the main objective, some hypotheses were elaborated and some variables were selected to confirm or not confirm it. Results showed that the strategic alignment was not found considering the industry as a whole, based on obtained sample. It was done analyzing the complete database e verifying, though advanced statistics methods, if the alignment was presented or not. However, using some additional mathematics and statistics tools, it was verified that some strategic aligned cases can be present in global sample or, at least, better results could be found instead of global database analysis. This can be the main contribution of this dissertation, to identify that strategic alignment can not be found in a complete sector but restricted to specific cases ou maybe predefined small groups